Perlindungan Hukum Terhadap Hak Cuti Panjang Pekerja di Grand Istana Rama Hotel - Sutarmayasa, I Kadek Putra (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2020)
The norm gap between the norms in the Act and those in reality namely the gap or discrepancy in the application of Article 79 of Law 13/2003 about regarding leave / long rest. Arrangements regarding the leave entitlement for employees at the Grand Istana Rama Hotel, namely Article 17 KKB of the Istana Rama Hotel, in addition to also being explained in article 79 of Law 13/2003, Kepmen 51/2004. The legal consequences for companies that do not provide workers with long-term leave entitlements are that the company must continue to provide workers with long-term leave / long-term leave in accordance with court decisions. This type of empirical legal research is used in this study to find out and understand the incompatibility of the application of Article 79 of the Manpower Act and Article 17 of the KKB Grand Istana Rama Hotel. Kesenjangan norma antara norma-norma dalam UU dan yang pada kenyataannya adalah kesenjangan atau perbedaan dalam penerapan Pasal 79 UU 13/2003 tentang cuti / istirahat panjang. Pengaturan mengenai hak cuti panjang bagi karyawan di Hotel Grand Istana Rama, yaitu Pasal 17 KKB di Hotel Istana Rama, di samping juga dijelaskan dalam pasal 79 UU 13/2003, Kepmen 51/2004. Akibat hukum bagi perusahaan yang tidak memberikan hak cuti jangka panjang kepada pekerja adalah bahwa perusahaan harus terus memberi pekerja cuti jangka panjang / cuti jangka panjang sesuai dengan keputusan pengadilan. Jenis penelitian hukum empiris digunakan dalam penelitian ini untuk mengetahui dan memahami ketidaksesuaian penerapan Pasal 79 UU Ketenagakerjaan dan Pasal 17 Hotel KKB Grand Istana Rama.